Visual approach of Malaysian animations from 1990s to 2000s / Khairul Azman - Azman, Khairul (2019)
This paper documents the development of visual or art approach of animated videos in Malaysia from the span of 1990s to 2000s. While Wayang Kulit arguably can be considered a pioneering Malaysian animation that has started at 1920s, this paper focuses specifically on the subject of cartoon animations that started around 1970s in Malaysia, where layers and frames of drawings and sketches were composited in an orderly manner, giving the illusion of movement. Animation in the Malaysian scene undoubtedly had a significant progress, where from a group of artists with little experience in animation working together in a studio set with cameras to a production team equipped with electronic devices. When the digital era (90s) arrived, computers came into hand and technologies and digital applications that are used for animation are becoming more and more user-friendly and powerful. Questions that came into mind are: “Have the subject matters become more eye-pleasing and intricate?”, “Are the movements and emotions more vivid?”, “Are there differences with the colour scheme?”, “What are the principles involved in the creation of characters?”. Therefore, analysing their method is important in understanding how technology, audience affects the quality of the animation. From the findings of this paper, the researcher will be able to utilize the accumulated data for the production of the final year project, whether to take inspiration from the predecessors or to revolutionise the way local society perceive the animation industry in Malaysia. In addition, one can learn to recognise the impact of the local animation industry in creating a formidable reputation as a creative hub in the Southeast Asia region.